2003
DOI: 10.1021/ac0207832
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Microwave Plasma Source Cavity Ring-Down Spectroscopy for Elemental Measurements

Abstract: We are exploring sensitive techniques for elemental measurements using cavity ring-down spectroscopy (CRDS) combined with a compact microwave plasma source as an atomic absorption cell. The research work marries the high sensitivity of CRDS with a low-power microwave plasma source to develop a new instrument that yields high sensitivity and capability for elemental measurements. CRDS can provide orders of magnitude improvement in sensitivity over conventional absorption techniques. Additional benefit is gained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…It has become a favored detection technique in elements analysis since the detection limits of ICP-atomic emission spectrometry (ICP-AES) and especially ICP-mass spectrometry (ICP-MS) are low. However, using ICP as an atomization cell for AAS measurement has some limitations [21]. Another plasma for the elements analysis is MIP; low detection limits also can be obtained [22].…”
Section: Introductionmentioning
confidence: 99%
“…It has become a favored detection technique in elements analysis since the detection limits of ICP-atomic emission spectrometry (ICP-AES) and especially ICP-mass spectrometry (ICP-MS) are low. However, using ICP as an atomization cell for AAS measurement has some limitations [21]. Another plasma for the elements analysis is MIP; low detection limits also can be obtained [22].…”
Section: Introductionmentioning
confidence: 99%
“…(192) Duan et al have investigated coupling an microwave induced plasma cavity ringdown spectroscopy (MIP-CRDS). (23) In that study, lead was chosen as a typical element for the system demonstration so that the results could be directly compared to those from an ICP-CRDS system. A detection limit of 0.8 ng mL −1 for Pb was obtained in that initial feasibility study.…”
Section: Microwave Induced Plasma Cavity Ringdown Spectroscopymentioning
confidence: 99%
“…Advantages of using a MIP instead of an ICP have been discussed extensively in our previous work. 28,29 Briefly, the MIP requires less electrical power and operating gas and also does not require a cooling system, important advantages when fieldability and portability are needed. We have also found that the MIP source is more stable than the ICP source for CRDS measurements.…”
Section: B Plasma Sourcementioning
confidence: 99%
“…The center wavelength for the mirrors is specified to be 620 nm with a reflectivity of 99.99%. For the 680 nm wavelength used in this effort, the maximum reflectivity of the mirrors is 99.9% and the effective reflectivity 26,29 is 99.85% when the plasma is on. The spacing between the longitudinal modes of this cavity is 0.0064 cm Ϫ1 , or 192.3 MHz.…”
Section: Ringdown Cavitymentioning
confidence: 99%
See 1 more Smart Citation